ETHICS AS A PHILOSOPHY OF SCIENCE (KNOWLEDGE) - Siregar, Fahrul (DERECHTSSTAAT, 2015)
ABSTRACTIt is a philosophy of ethical values, morality, about good and bad. In addition to studying the ethical values, as well as a knowledge of the values themselves. Some say that ethics is part of a philosophy that teaches the whole mind (good and bad). The concept of ethics as a field of study of philosophy, especially moral philosophy, ethics has very long been the intellectual discourse of the philosophers. Ethics has become the center of attention since the days of ancient Greece. Until now, even ethics still be interesting and actual field of study. Even considered semankin important to not just talk in academic circles but also practiced in daily life interactions every civilized ma. Keywors : Ethics, Philosophy of Science